Faktor Pengaruh Pembelajaran E-Learning Progdi S1 Akuntansi Universitas Pamulang - I Gede Adi Indrawan; Juitania Juitania; Raden Ai Lutfi Hidayat (SAP (Susunan Artikel Pendidikan), 2021)
The Indonesian government implements Large-Scale Social Restriction known as PSBB which impacts the teaching and learning process at various levels of education to be disrupted as a result of school off in anticipation of the spread of COVID-19 in line with the implementation of the Regulation of the Minister of Health (Permenkes) RI Number 9 of 2020, the process of teaching and learning activities in various educational institutions have been temporarily suspended and replaced with online learning as imposed by Pamulang University by implementing E-Learning. The aim of the research is to explain the relevant aspects of the observed phenomenon by describing the effect of student motivation and interest in learning on e-learning methods by Pamulang University,  Bachelor of Accounting Study Program, Academic Year of 2020/2021 through observation activities, as well as questionnaires followed by validity tests and reliability tests. The research was classified as a quantitative research. The data analysis used in this research was descriptive statistics and causality. The result showed that the effect of motivation and learning interest have positive and significant influence on e-learning in Bachelor of Accounting Program in Pamulang University. In other words, E-Learning activities will run optimally if students motivation and interest in learning can be maintained properly.